Politeness Strategies In Disagreement Used By English Department Students Of Muhammadiyah University Of Surakarta - Gaspie, Renaldo, Dra. Siti Zuhriah Ariatmi, M.Hum, Agus Wijayanto, Ph.D (2014)
This research aims at describing the use of politeness strategy in disagreement used by English Department students. The study used descriptive qualitative research which includes fifty students at seventh semester at English Department Muhammadiyah University of Surakarta. The data are disagreement utterances collected form interviewing by using Discourse Completing Task (DCT) as the instrument. The subjects are taken using random sampling which consists of twenty five male students and twenty five female students. The data are studied by using Brown and Levinson's politeness strategy, Pomerantz's disagreement theory, and Wardhaugh's social distance and social level theory. Based on the research finding, the researcher found that bald on record (BOR) is the most appeared politeness strategy which has value as 64,66%. The second place is negative politeness (NP) as 16,89%. The third place is off record (OR) as 10,11%and the last one is positive politeness (PP) as 8,33%. The researcher found that male students use higher value of BOR than female students, while female students use greater value of NP than male students. Both social distance and status level affect to the type of politeness strategy. Social distance makes the use of negative politeness becoming greater. Stratus level makes the use of BOR less appeared. Social status also makes the use of NP becoming greater. In using disagreement, almost all of the participants uses strong form of disagreement instead of using the weak form.